Financing Infrastructure in India : Macroeconomic Lessons and Emerging Market Case Studies - Walsh, James; Park, Chanho; Yu, Jiangyan (Washington, D.C. : International Monetary Fund, 2011)
Driving infrastructure development, notably mobilizing financial resources for infrastructure projects, has been challenging in many countries. This study includes two parts: an empirical analysis of macroeconomic risks associated with infrastructure booms, and a case study of four emerging economies about their practice of funding infrastructure development. The study shows that (i) there is no empirical evidence that rapid infrastructure growth would undermine contemporary macroeconomic performance, implying that room is created to accommodate infrastructure booms without compromising fiscal and external sustainability; (ii) banks may play an important role in financing infrastructure, but caution is needed to avoid directed lending and regulatory forbearance that the authorities may use to promote financing; (iii) capital market development is important to accommodate the usually high financing needs, and encouraging private investors to move into infrastructure would require regulatory and institutional improvements; and (iv) public support, including credit guarantees, may help bolster investors' confidence, but the authorities should carefully monitor and manage fiscal risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet